Refleksi Mahasiswa Terhadap Pembelajaran Mata Kuliah Islam Rahmatan Lillamin - Syahdara Anisa Makruf (UMSU, 2021)
The Islamic rahmatan Lil Alamin course is a compulsory subject given to students at the Islamic University of Indonesia. This course is an important supporter to create graduates with ulil albab character. So far, there has been no research on reflections submitted by students to this course. This research was conducted with a descriptive qualitative approach. The results show that students believe that the Islamic course rahmatan Lil Alamin explains Islam is a religion that includes all aspects of life, has universal human values, and respects each other. In terms of lecture material can provide benefits to improve personal and social life. In addition, the case study approach can trigger students to be active in discussing in class.